Community Empowerment with Stunting Risk Factors Based on Home visit Approach: Scoping Review - Resya Aprillia; Andari Wuri Astuti; Siti Fatimah; Lulu Annisa; Lantiar Winda Oktari Pondawati; Tamela Zahra; Cindy Putri Febrianti; Tima Hajar Arofah (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: Stunting is one of the health problems of children in the world, including Indonesia. Empowerment is the encouragement of knowledge and the role of individuals in opportunities, participation, and increasing access to health to improve the quality of life. Purpose: This study aims to find scientific evidence related to community empowerment with risk factors for stunting through a home visit approach. Methods: The literature search from 3 databases, Pubmed, ScienceDirect, Wiley Online Library and also using grey literature from Google Scholar, the inclusion criteria is primary articles from 2017-2022, articles in English and original articles on the topic Community Empowerment with Stunting Risk Factors through the Home visit Approach. This study used the Joanna Bridge Institute (JBI) critical appraisal tool to assess the quality of articles. Results: The first 1711 articles obtained then selected into 7 articles that were eligible used a qualitative and mixed methods research design. Mapping the themes and Sub themes obtained from the analysis of the article is the first themes pattern of parenting of subthemes feeding practice, and second themes is socio-demographic aspects of subthemes knowledge, mother’s autonomy in decision making, socio economics, clean water sanitation and disposal. Conclusion: Targeted community empowerment is expected to reduce the factors that influence the incidence of stunting such as parenting through feeding and sociodemographic aspects which are strongly influenced by knowledge, the mother’s autonomy in decision making, social economy, and environmental sanitation factors. The existence of community empowerment with stunting risk factors aims to increase opportunities, participation, and access to health services.